Bed protection below culvert outlets - Ma, Yin (2010)
Riprap continues to be the most widely used method for protection of erodible channel boundaries. In this report, an experimental study was conducted to understand the mechanisms and characteristics of scour without protection below culvert outlets, and thereby investigating a suitably sized riprap protection for the bed material to reduce the scouring effect of the jet flow.